REKLAMASI PULAU K DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN DAN KEKUATAN HUKUM IZINNYA - Untoro Untoro; Hamdan Azhar Siregar (ADHAPER: Jurnal Hukum Acara Perdata, 2018)
Land reclamation over the coast has four philosophically values, among others is that reclamation must observe prevailing regulations. An administrative lawsuit has been lodged into Jakarta Administrative Court against the Governor of Jakarta Decree No. 2485 of 2015 concerning License on K Island Reclamation. The problems arose over the case both legally, socially, and philosophically. This article will examine the Administrative Court consideration over the case, especially on the issues of the implication of Governor’s license, coastal region use in the perspective of sustainable development, and the implication of license towards the case pending before civil court. The research methodology uses normative research. The research ﬁ nds that the license issued by the Jakarta Governor comply with Article 93(1) of Law No. 32 of 2009 concerning Protection and Management of Living Environment. The use of coastal region should be directed for the achievement of sustainability of ecology, economy, social, and cultural. The implication of license related to civil case has a correlation that the licensee cannot freely doing reclamation even though he holds a license. The licensee must observe the impact of reclamation over surrounding environment. A civil lawsuit based on unlawful act committed by the licensee can be submitted if the reclamation inﬂ icts ﬁ nancial loss to the surrounding community.